The "Carbonyl Story" and Beyond; Experiences, Lessons and Implications. (2nd September 2020) - Alberto, Roger
Abstract: The complex [ 99m Tc(OH2 )3 (CO)3 ] + has become a versatile building block in radiopharmaceutical chemistry, applied by many groups worldwide. However, despite widespread efforts, only one compound has made it right the way through clinical trials. Along the way from its discovery to its development into an eventual product, the author experienced issues that he would handle differently in retrospect. In this article, these experiences are turned into "lessons" that might be helpful for young researchers finding themselves in similar situations. Beside issues with patenting and company strategies, the carbonyl story has provided scientific implications beyond its own story, and insights from which any future 99m Tc‐based chemistry for radiopharmacy or molecular imaging might benefit. Abstract : Lessons in discovery and development : The way to bring a 99m Tc imaging agent into and through clinical trials is a long one. Although "carbonyl technology" has been known for almost two decades, only one compound made it that far. The different reasons for this are discussed in the paper together with scientific developments inspired by but beyond the carbonyl technology.